Visual analysis of canned alcoholic beverages' packaging to avoid confusion among muslim consumers / Mohd Nasiruddin Abdul Aziz - Abdul Aziz, Mohd Nasiruddin (2015)
Islam is the official religion in Malaysia and alcoholic drinks is totally illegal for Muslims. Several cases have been reported in newspaper about the mixed placement of alcoholic and non-alcoholic canned beverages at the same product shelf. The design on the cans caused the confusion among Muslim consumers to differentiate between the alcoholic and non-alcoholic canned beverages. This research aimed to define the confusing elements and create a new visual sign to help the Muslim consumers to be able to recognize the canned alcoholic beverages effectively. The research use mixed method to achieve the research objectives. The qualitative data gathered from questionnaire survey in pilot-test, pre-test, and post-test stages, while the quantitative data are from literature review, in-depth interview, direct observation, and visual analysis. All collected data was analysed and integrated using the triangulation of data. The early research found that there are five design elements may cause the confusion which is pattern, colour, brand, images, and typography. A Haram logo was developed to enhance the contrast design between Halal and Haram canned beverages. It is hoped that this research will encourage other local researchers to investigating on this related issue to ensure the Malaysian Muslim consumers right always in protected.